TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENYELEWENGAN DANA DESA : Studi pada Polres Lampung Barat - M. Ruhly Kesuma Dinata; Irhammudin (Legalita, 2022)
In accordance with Article 72 of Law 6 of 2014 concerning Rural Areas, village income sourced from the APBN or village funds comes from central spending by increasing the efficiency and equity of village programs. The amount of the budget allocation that is allocated directly to the village is set at 10%. the amount paid to the area (above). In addition, Law Number 6 of 2014 also strengthens the allocation of village funds (ADD) from district/city balancing funds. Given the enormous power of the village head in administering village government based on the Decree of the Government of the Republic of Indonesia Number 72 of 2005 Article 14, it is necessary to review and balance the administration of village governance. The agency authorized to supervise village heads on village household expenditures is the BPD. The role of the village council as the controlling body of the village government requires responsibility and ability in carrying out its duties. It is also clear that according to the Decree of the Government of the Republic of Indonesia Number 72 of 2005, the BPD is an institution that embodies democracy under the leadership of the village government as part of the village administration with the village head.